The Effect of Increased Pork Hot Carcass Weights and Chop Thickness on Consumer Visual Appearance and Purchase Intent Ratings of Top Loin Chops - E. A. Rice; A. B. Lerner; H. E. Price; J. C. Woodworth; M. D. Tokach; S. S. Dritz; R. D. Goodband; J. M. DeRouchey; M. W. Allerson; J. M. Gonzales; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2018)
The objective of this study was to evaluate the effect of increased pork hot carcass weights on consumer visual acceptability and purchase intent of top loin chops cut to various thicknesses in a price labeled versus unlabeled retail display scenario. Pork loins (n = 200) were collected from 4 different hot carcass weight groups: a light weight group (less than 246.5 lb; LT), medium light weight group (246.5 to 262.5 lb; MLT), medium heavy weight group (262.5 lb to 276.5 lb; MHVY), and heavy weight group (276.5 lb and greater; HVY). Loins were fabricated into 4 pairs of chops of specified thicknesses (0.50, 0.75, 1.00, and 1.25 inches) at day 7, 8, and 9 postmortem. One chop from each specified thickness was then randomly assigned to be packaged with a label and the other to be packaged without a label. Consumers (n = 393; 8/panel) from the Manhattan, KS, area assessed chops from each weight group × thickness combination in both labeled and unlabeled scenarios. Chops were assessed on a 1 to 100 continuous line scale for desirability and purchase intent. Consumers were also able to indicate if the chop was either desirable or undesirable and if they would or would not purchase. Consumers gave greater (P<0.05) appearance ratings to chops from HVY and MHVY weight group compared to chops from the LT weight group. Additionally, chops with a thickness of 1.00 and 1.25 were similar (P>0.05) and had greater (P<0.05) consumer appearance ratings than both 0.75- and 0.50-inch chops. For purchase intent ratings, consumers gave greater (P<0.05) ratings to chops from HVY and MHVY carcasses compared to chops from LT carcasses. Consumers gave chops with a thickness of 0.50 inches the lowest (P<0.05) purchase intent ratings compared to all other thicknesses. There was a carcass weight × chop thickness interaction (P<0.05) for the percentage of consumers who indicated “Yes” the chop was desirable overall. For all weight treatments, 0.50-inch chops had the lowest (P<0.05) percentage of consumers who indicated the chop was desirable. A greater (P<0.05) percentage of consumers indicated they would purchase 1.00-inch chops compared to all other thicknesses, with 0.75- and 1.25-inch chops intermediate (1.00>0.75>1.25>0.50). Additionally, a greater (P<0.05) percentage of consumers indicated they would purchase unlabeled chops compared to labeled chops. These results indicate that carcass weight and chop thickness can affect consumer preference and purchasing decisions and thus should be considered by retailers when marketing fresh pork loin chops.
Keywords: consumer preference; heavy pigs; hot carcass weight; pork quality; visual